Unveiling the Merdeka Curriculum: A Review of Local Wisdom Integration in Civic Education for Junior High Schools - ‎ , Sakman; Abdulkarim, Aim; Komalasari, Kokom; Masyitoh, Iim Sitti (KnE Social Sciences, 2024)
This research presents a literature review about the integration of local wisdom into Civics learning in junior high schools with an independent curriculum to strengthen Indonesia’s national identity. Through a deep understanding of local wisdom, students can develop a sense of pride in their cultural heritage. This can help strengthen national unity and prevent social disintegration. Besides, the integration of local wisdom can also help raise students’ involvement in the Civics learning process, because material that is relevant to the local context will be easier for students to understand and identify. The literature used in this study comprises 2 books and 30 articles from relevant journals. Based on the results of the review, it can be concluded that the integration of local wisdom into Civics learning can be done by incorporating local wisdom values into Civics material according to the “Theme” or “Topic”. Meanwhile, the hidden curriculum of local wisdom can be included in regulations, norms, and learning rules; for example, in the learning process, students must behave based on existing local wisdom values. This will make learning more meaningful because the material studied is relevant to the context of community life and students discover local values that are relevant to life through interaction with their environment. Keywords: local wisdom, civics learning, independent curriculum